Conservation : RIBA plan of work 2013 guide - Feilden, Hugh (Newcastle upon Tyne : RIBA Publishing, 2017)
'Conservation' is part of a brand new series providing must-read practical guidance to running efficient and successful projects using the new RIBA Plan of Work 2013. Each guide takes a particular angle - in this case the author guides you through working on a conservation project - and explains the essential activities required at each stage.
Foreword Series editor's foreword Acknowledgements and dedication About the Author and Series Editor Introduction The RIBA Plan of Work 2013 Stage 0. Strategic Definition Stage 1. Preparation and Brief Stage 2. Concept Design Stage 3. Developed Design Stage 4. Technical Design Stage 5. Construction Stage 6. Handover and Close Out Stage 7. In Use Further Reading Topic Glossary Plan of Work Glossary Index
Includes index.
ARC
Keywords: Architecture and energy conservation; Architecture and Planning; Architecture